Validasi Instrumen Skala Hambatan dalam Memperoleh Bantuan Psikologis untuk Kebutuhan Layanan Bimbingan dan Konseling di Sekolah - Parti, Nidya Juni (Jurnal Fokus Konseling, 2018)
The barriers associated with psychological relief search are defined as a general aversion to receiving psychological help or factors that inhibit psychological help-seeking behavior. The purpose of this study was to validate the scale of barriers in obtaining psychological assistance for the need for guidance and counseling services in schools. In line with this objective, the validity and reliability of the scale were examined in five different studies. The results of the validity and reliability test show that the scale consists of five dimensions, which are labeled as fear of stigmatization by society, trust in mental health professionals, difficulties in self-disclosure, devaluation perceptions and lack of knowledge. Subjects in this study amounted to 37 students. The findings indicate that the barriers to obtaining psychological support for school counseling and guidance needs are valid and reliable instruments for measuring student barriers in obtaining psychological assistance that school counselors will then use for school guidance and counseling services. Keywords:  validity, student barriers, psychological help, guidance and counseling                   service needs in school.